FAKTOR-FAKTOR YANG MEMPENGARUHI TURNOVER INTENTION (Studi Pada Karyawan Perusahaan Jasa Multi Finance Di Kota Jambi) - Ahmad Firdaus (Universitas Batanghari Jambi, 2017)
This research aims to know the factors that affect employee turnover intention on multi services companies in finance in the city of jambi. The study is quantitative research is an investigation about the social issues based on testing a theory consisting of variables, measured by numbers, and analyzed with statistical procedures to determine whether the correct theory of the predictive generalizations. The respondents in this study i.e., employees at the companies services multi finance in the city of Jambi, the method of withdrawal of samples in this study using a purposive samplingmethod, the author here use qualitative data are ordinal by disseminating the questionnaire covered alternative answer had been provided to the respondent, the dataare transformed into data interval and processed with path analysis, the results of this research show the two factors which effect on the turnover intention, namely factors of job satisfaction and organizational commitment the second, of the most influential factors i.e. organizational commitment factor. Keywords: Turnover Intention